Influence of the method of postactivation stimulation on the performance of ski jumping from springboards of various capacities by highly qualified athletes - Kryuchkov A.S.; Avvakumova I.A.; Fendel T.V.; Zubkov D.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the impact of exercises performed by highly qualified female athletes within the framework of the post-activation stimulation method on the performance of ski jumping from springboards of various powers. Methods and structure of the study. The pedagogical experiment was conducted with the participation of six representatives of the Russian national ski jumping team (4 masters of sports, 1 international master of sports and 1 honored master of sports). The experiment was carried out in the 2023-2024 season (preparatory period). The effectiveness of performing jumps from springboards of various power was assessed by the method of control tests (ski jump from a springboard). The final score included a range score and a technique score. The influence of three sets of exercises performed within the framework of the post-activation stimulation method on the performance of jumping from springboards of various power was assessed using the Spearman pair correlation method. Results and conclusions. In the process of preparing to perform low-power springboard jumps (K-60), it is advisable to use exercises performed using the post-activation stimulation method, aimed at increasing the power of muscle contraction (in this case, the jump distance increases) and aimed at improving the biodynamics of movement (technique scores increase). In the process of preparing for performing medium-power springboard jumps (K-90), it is advisable to use any variants of the post-activation stimulation method (they have a positive effect on both the jump distance and marks for technique), and for performing high-power springboard jumps (K-120 ) it is advisable to use exercises performed by the method of post-activation stimulation, aimed at improving technique (in this case, the jump distance increases) and aimed at improving the biodynamics of movement (scores for technique increase). Exercises performed by the post-activation stimulation method have different effects on the performance of highly qualified female athletes ski jumping from springboards of varying power.